Rapid metagenomic identification of viral pathogens in clinical samples by real-time nanopore sequencing analysis. Issue 1 (December 2015) - Greninger, Alexander; Naccache, Samia; Federman, Scot; Yu, Guixia; Mbala, Placide; Bres, Vanessa; Stryke, Doug; Bouquet, Jerome; Somasekar, Sneha; Linnen, Jeffrey; Dodd, Roger; Mulembakani, Prime; et al.
Abstract We report unbiased metagenomic detection of chikungunya virus (CHIKV), Ebola virus (EBOV), and hepatitis C virus (HCV) from four human blood samples by MinION nanopore sequencing coupled to a newly developed, web-based pipeline for real-time bioinformatics analysis on a computational server or laptop (MetaPORE). At titers ranging from 107 –108 copies per milliliter, reads to EBOV from two patients with acute hemorrhagic fever and CHIKV from an asymptomatic blood donor were detected within 4 to 10 min of data acquisition, while lower titer HCV virus (1 × 105 copies per milliliter) was detected within 40 min. Analysis of mapped nanopore reads alone, despite an average individual error rate of 24 % (range 8–49 %), permitted identification of the correct viral strain in all four isolates, and 90 % of the genome of CHIKV was recovered with 97–99 % accuracy. Using nanopore sequencing, metagenomic detection of viral pathogens directly from clinical samples was performed within an unprecedented <6 hr sample-to-answer turnaround time, and in a timeframe amenable to actionable clinical and public health diagnostics.